Self-assembled liquid crystalline nanotemplates and their incorporation in dye-sensitised solar cells - Kamarudin, M.A.; Khan, A.A.; Williams, C.; Rughoobur, G.; Said, Suhana Mohd; Nosheen, S.; Flewitt, A.J.; Qasim, M.M.; Wilkinson, T.D. (Elsevier, 2016)
Liquid junction dye-sensitised solar cells (DSSCs) suffer from solvent evaporation and leakage which limit their large-scale production. Here, we have prepared DSSC using a simple and cheap fabrication process with improved photovoltaic parameters and stability. A binary mixture of Smectic A (SmA) and Nematic Liquid Crystal (NLC) was used to provide a self-assembled template for a polymerisable reactive mesogen LC. The layered structure of SmA combined with a low viscosity NLC forms a polygonal structure that provides an ordered and continuous template for reactive mesogens. Once the reactive mesogen is polymerised under UV light, the SmA:NLC mixture is washed away, resulting in a polymer network template containing nanochannels. We demonstrate the incorporation of these templates into DSSCs and find that DSSCs containing these nanochannels show improved open-circuit voltage (VOC) (0.705 V) and short-circuit current (JSC) (13.25 mA cm−2) compared to that of the liquid electrolyte (VOC = 0.694 V and JSC = 10.46 mA cm−2). The highest obtained power conversion efficiency with Sm-PE was 5.94% which is higher than that of the reference solar cell (5.51%). These can be attributed to the improved ionic conductivity and ionic diffusion of Sm-PE where the presence of the nanochannels aided the ionic conduction in the polymer electrolyte. In addition, it is hypothesized that the light scattering effect of the polymerised reactive mesogen also contributed to the improved performance of the photovoltaic devices. This finding is important because it is known fact that when a polymer is added to liquid electrolyte, the ionic conductivity will decrease although the stability is improved.